Distinguishing The False Gospel And The True Gospel: Analysis Syntax And Semantics In Galatians 1:6-9 - Ririn Valentine; Hendi Wijaya (Sekolah Tinggi Teologi Moriah, 2022)
The gospel is a message of good news that originates with God and is directed toward his glory. Paul warned the Galatians in Galatians 1:6–9 not to trust in the false gospel in order to save them from destruction. What false gospel is that, and what is its difference from the true Gospel, he questioned after stating the fundamental issue? The purpose of this study is to clarify the differences between the true and false gospels (Gal. 3:1). The method of research used is exegesis, which involves analyzing text through its syntax and semantics. The results of the author's research that the fake Bible is a false gospel is a gospel that turns away from grace, is human - centered (v. 6-7), and is cursed (v. 8-9). However, the true gospel is one that is based on grace in order to please God and lead to salvation through faith.